2000
DOI: 10.1095/biolreprod62.3.781
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Vasodilator Production by Uterine and Systemic Arteries. IV. Cyclooxygenase Isoform Expression During the Ovarian Cycle and Pregnancy in Sheep1

Abstract: Uterine artery endothelial production of the potent vasodilator, prostacyclin, is greater in pregnant versus nonpregnant sheep and in whole uterine artery from intact versus ovariectomized ewes. We hypothesized that uterine artery cyclooxygenase (COX)-1 and/or COX-2 expression would be elevated during pregnancy (high estrogen and progesterone) and the follicular phase of the ovarian cycle (high estrogen/low progesterone) as compared to that in luteal phase (low estrogen/high progesterone) or in ovariectomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 56 publications
(169 reference statements)
6
32
0
Order By: Relevance
“…14 In another study treatment of fetal ovine pulmonary artery endothelial cells with 17␤-estradiol in vitro increased COX-1 mRNA and protein with a concomitant elevation of both basal and stimulated PGI 2 synthesis. 11 This was shown to be due to increased transcription and translation and not to changes in stability of mRNA or protein.…”
Section: Ospina Et Almentioning
confidence: 96%
See 1 more Smart Citation
“…14 In another study treatment of fetal ovine pulmonary artery endothelial cells with 17␤-estradiol in vitro increased COX-1 mRNA and protein with a concomitant elevation of both basal and stimulated PGI 2 synthesis. 11 This was shown to be due to increased transcription and translation and not to changes in stability of mRNA or protein.…”
Section: Ospina Et Almentioning
confidence: 96%
“…13 Moreover, fluctuating estrogen levels that occur during the menstrual cycle cause parallel changes in PGI 2 synthesis in uterine blood vessels. 14 Given that cyclooxygenase-dependent pathways are important in the regulation of cerebral blood flow, 15 it is interesting that the effects of 17␤-estradiol on PGI 2 production in the cerebral vasculature have not previously been studied.…”
mentioning
confidence: 99%
“…However, this action of estrogen may vary according to the vascular bed being studied. For example, increases in COX-1 expression or prostacyclin synthesis were seen in uterine (107,111), aortic (110), pulmonary (109) and umbilical (108) tissue, but not omental (107) and vascular tissue. In mesenteric vessels, one study reported E 2 to be associated with a diminished prostanoid-dependent vasodilating function (112), while another provided evidence for an E2-related capacity to repress prostanoid-associated vasoconstrictor function (113).…”
Section: +mentioning
confidence: 99%
“…In the vast majority of experiments, cells were exposed to estradiol during 24-48 hours, and the increase of prostacyclin above control values ranged from 16 % to 78 % (Table 1). In addition, it has been shown that estradiol stimulates production of prostaglandins in a variety of preparations of arteries, including ovine uterine arteries (Vagnoni & Magness, 1998;Janowiak et al, 1998;Habermehl et al, 2000), mesenteric arteries from ovariectomized rats (Davidge & Zhang, 1998;Armstrong et al, 2002), rat cerebral blood vessels (Ospina et al, 2002;Ospina et al, 2003), and aorta from ovariectomized monkeys (O'Sullivan et al, 2001). The increase of prostacyclin production is of a similar magnitude to that obtained with cultured endothelial cells.…”
Section: Delayed (Genomic) Effects Of Estrogens On Prostanoids Vasculmentioning
confidence: 69%
“…In this way, COX-1 protein content is increased in rat (Ospina et al, 2002) and mice (Geary et al, 2001) cerebral blood vessels, and in ovine uterine arteries in response to treatment with estrogen (Rupnow et al, 2002). Indeed, COX-1 (but not COX-2) expression is increased in the endothelium of the ovine uterine artery during the follicular phase of the ovarian cycle and during pregnancy, where estrogen levels are highest (Janowiak et al, 1998;Habermehl et al, 2000). In spite of the classic consideration of COX-2 as an inducible enzyme, it seems that COX-2 does not contribute to the estradiol-increased prostacyclin production.…”
Section: Delayed (Genomic) Effects Of Estrogens On Prostanoids Vasculmentioning
confidence: 93%